Digital Skills in Technical and Vocational Education: A Data-Driven Analysis of TVET Competency Trends - Rahmawati, Sherly; Abdullah, Ade Gafar; Widiaty, Isma (Journal of Vocational Education Studies, 2025)
In the age of digital transformation, digital competence has become crucial for vocational educators to effectively align learning practices with the changing demands of the industry. This study aims to analyze the global development and thematic trends surrounding digital competence in Technical and Vocational Education and Training (TVET) through a combined approach of bibliometric analysis and a systematic literature review, referred to as Systematic Literature Network Analysis (SLNA). Utilizing Scopus as the primary database, the research retrieved 216 articles and employed bibliometric visualization tools (Bibliometrix, Biblioshiny, VOSviewer) alongside eligibility criteria-based screening for the systematic review. The results reveal three key insights: (1) significant connections between digital competence and the advancement of AI in vocational education, (2) the emerging importance of interaction and social competence in enhancing digital literacy, and (3) the limited yet essential integration of AI literacy within current digital competence frameworks. Two selected articles from the systematic literature review suggest that the combination of digital and social competencies is vital for preparing vocational teachers and students for the demands of a technology-driven workforce. This study underscores the necessity for a forward-looking digital competence framework that addresses the interplay between digital skills, social skills, and AI readiness within vocational education contexts.